THE EFFECT OF ORGANIZATIONAL ACTIVITY ON THE DEVELOPMENT OF STUDENTS' SOFT SKILLS. A CASE STUDY OF HPPMI CADRES MAROS UNIVERSITAS NEGERI MAKASSAR COMMISSION. - Muhammad Isfar Nur Fajar; Anwar Ramli; Agung Widhi Kurniawan; Widhi Nugraha Sumiharja Darmawinata (Jurnal Manajemen, 2026)
Abstract: This study aims to analyze the influence of organizational activity on the development of students' soft skills in the regional organization of the Indonesian Student Youth Association (HPPMI) Maros Commissariat, Makassar State University. In addition, this study also aims to determine the contribution of organizational activity to the development of students' soft skills. This study uses a quantitative approach with a causal associative research design. The study population was all cadres of HPPMI Maros Commissariat, Makassar State University, totaling 59 people. The sampling technique used saturated sampling so that the entire population became research respondents. Data collection techniques were carried out through distributing questionnaires using a Likert scale. The data obtained were then analyzed using simple linear regression analysis. The results showed that organizational activity had a positive and significant effect on the development of students' soft skills of HPPMI Maros Commissariat, Makassar State University. The coefficient of determination value shows that organizational activity contributed 81.7% to the development of students' soft skills, while the rest was influenced by other factors outside the research model. These findings show that the higher the level of student activity in organizational activities, the higher the level of soft skill development that students have. Keywords: Organizational Activity, Soft Skills, Student Organizations, Self-DevelopmentKeywords: Organizational Activity, Soft Skills, Student Organizations, Self-Development